Electrochemically Reduced Graphene Oxide‐Sheltered ZnO Nanostructures Showing Enhanced Electrochemical Performance Revealed by an In Situ Electrogravimetric Study. Issue 5 (22nd January 2019) - Gao, Wanli; Demir‐Cakan, Rezan; Perrot, Hubert; Sel, Ozlem
Abstract: The present work is on the synthesis and characterization of vertically aligned ZnO nanostructures sheltered by electrochemically reduced graphene oxide (ERGO), i.e., ZnO@ERGO, which are directly generated on quartz resonators of microbalance sensors. The vertical orientation of the ZnO nanorods is achieved by a two‐step synthesis method involving an electrochemically grown seed layer and a subsequent hydrothermal growth. Deposited ERGO thin layer turns out to be highly effective to enhance the electrochemical performances of vertically oriented ZnO nanorods as supercapacitor electrodes. The interfacial charge storage mechanism of ZnO@ERGO electrodes with unique architecture is first studied by classical electrochemical quartz crystal microbalance (EQCM), showing a global cation‐exchange behavior in Na2 SO4 electrolyte. A complementary technique, electrogravimetric impedance spectroscopy, is then used to deconvolute the EQCM response into individual contributions from Na + ·H2 O, SO4 2−, and H2 O molecules, offering a quantitative picture of each participant in the charge balance process with their transfer kinetics. Abstract : The ZnO@ERGO (electrochemically reduced graphene oxide) nanocomposites are fabricated directly on the quartz resonators. A thin ERGO sheltering onto ZnO nanostructures noticeably enhances the electrochemical performance of the pristine ZnO electrode. The multispecies contribution into the interfacial charge storage behavior of electrodes with such complex architecture is revealed by electrogravimetric methods, coupling quartz crystal microbalance to electrochemical methods.